Attention induction based on pathologist annotations for improving whole slide pathology image classifier - Ryoichi Koga; Tatsuya Yokota; Koji Arihiro; Hidekata Hontani (Journal of Pathology Informatics)
We propose a method of attention induction to improve an attention mechanism in a whole slide image (WSI) classifier. Generally, only some regions in a WSI are useful for lesion classification, and the WSI classifier is required to find and focus on such regions for the classification. Multiple instance learning and hierarchical representation learning are widely employed for WSI processing and both use attention mechanisms to automatically find the useful regions and then conduct the class prediction. Here, it is impractical to collect a large number of WSIs, and when the attention mechanism is trained with a small number of training WSIs, the resultant attention often fails to focus on the useful regions. To improve the attention mechanism without increasing the number of training WSIs, we propose a method of attention induction for a hierarchical representation of WSI that guides attention to focus on the regions useful for lesion classification based on pathologist's coarse annotations. Our experimental results demonstrate that the proposed method improves the attention mechanism, thereby enhancing the performance of WSI classification.